Key factors in African climate change evaluated by a regional climate model - Paeth, Heiko (ERDKUNDE, 2004)
Rainfall variability and scarce freshwater availability represent the major limiting factors for West African economies and ecosystems. Given a remarkable increase in population density and agricultural needs, it is of basic importance to improve our knowledge of the climatic processes, which affect the amount and distribution of rainfall over tropical and subtropical Africa. The present study is dedicated to the main players in African climate variability with special emphasis on future climate changes. A regional climate model is run over Africa in order to quantify and compare the individual effects of oceanic heating, greenhouse forcing, vegetation loss and soil degradation with each other. The numerical model is found to reproduce the recent climate in excellent agreement with the observations. Especially, the simulated monsoon circulation and rainfall distribution are most realistic. Rainfall variability is primarily related to changes in the tropical sea surface temperatures (SSTs). A warm oceanic surface is generally associated with abundant rainfall in the coastal areas of tropical West and East Africa, whereas dryer conditions prevail over the Sahel Zone and the Congo Basin. Since increasing greenhouse-gas (GHG) concentrations directly heat up the tropical oceans, global warming is likely to induce exactly this pattern of precipitation anomalies at the end of the 21st century. A reduction in vegetation cover is partly counteracting the GHG forcing with deficient rainfall over the entire subcontinent. Related changes in the soil properties additionally contribute to a deterioration of freshwater availability. A local change in land cover is directly linked to a local anomaly of the hydrological cycle - a matter which is of high relevance to political measures and plannings.